Key Skills Leader in Cell Public Procurement - Borowiec , Arkadiusz (Studia Oeconomica Posnaniensia, 2016)
The public procurement system confronts personnel managers in public procurement cells with high competence in planning and organizing tender procedures. Accordingly, the selected article-no key factors were associated with this process. For this purpose, ba-dishes for 85 officials of various levels of employment in public administration at the position of the contracting authority were conducted. Purposeful selection was attempted, to gather as many competent people familiar with the specific response of the profession and the elimination of circulation and subjective views of people outside it. After being selected by the respondents, the most important factors were analyzed in accordance with the methodology of thinking power, which allowed the isolation of active and critical factors, which, due to their effectiveness, have been identified as key. The role of experts during the analyses carried out using that methodology created 32 postgraduate students in public procurement and public-private partnerships. These students represented both public administration and the contractors participating in the tenders. Such a sample in terms of subjective assumptions corresponds to the methodology, which assumes the divergence of positions and looks at the problem, analyzed from different perspectives.